CS-24 Association of lipoprotein subfractions and glycoprotein acetylation with coronary plaque burden in systemic lupus erythematosus. (August 2018) - Purmalek, Monica M; Carlucci, Philip M; Dey, Amit K; Sampson, Maureen; Temesgen-Oyelakin, Yenealem; Sakhardande, Simantini; Lerman, Joseph B; Fike, Alice; Davis, Michael; Chung, Jonathan H; Salahuddin, Taufiq; Manna, Zerai; et al.
Abstract : Background: Subjects with Systemic Lupus Erythematosus (SLE) display an increased risk of atherosclerotic cardiovascular disease (CVD) that is not explained by Framingham Risk. This study sought to investigate the utility of nuclear magnetic resonance (NMR) spectroscopy measurements of serum lipoprotein particle counts and size and glycoprotein acetylation (GlycA) to predict coronary atherosclerosis in SLE. Methods: Coronary plaque burden was assessed in SLE subjects and healthy controls using coronary CT angiography. Lipoproteins and GlycA were quantified by NMR spectroscopy. Results: SLE subjects displayed statistically significant decreases in high-density lipoprotein (HDL) particle counts and increased very low density lipoprotein (VLDL) particle counts compared to controls. Non-calcified coronary plaque burden (NCB) negatively associated with HDL subsets, whereas it positively associated with VLDL particle counts in multivariate adjusted models. GlycA was significantly increased in SLE sera compared to controls. In contrast to high-sensitivity C-reactive protein, elevations in GlycA in SLE significantly associated with NCB and insulin resistance. Conclusions: SLE patients display a proatherogenic lipoprotein profile that may significantly contribute to the development of premature CVD. The results demonstrate that NMR measures of GlycA and lipoprotein profiles, beyond what is captured in routine clinical laboratory tests for lipids, could be a useful tool in assessing CVD risk in SLE patients.